LRRC75A antisense lncRNA1 knockout attenuates inflammatory responses of bovine mammary epithelial cells - Wang, Xixi (Int J Biol Sci, 2020)
Long noncoding RNAs (lncRNAs) play multiple key roles during inflammatory processes. In this study, a novel lncRNA identified by the high-throughput sequencing analysis was found significantly down-regulated in Escherichia coli-introduced cell model of bovine mastitis. Given that this lncRNA consists of the antisense of leucine-rich repeat-containing protein 75A (LRRC75A), it was named LRRC75A antisense lncRNA1 (LRRC75A-AS1). The expression of LRRC75A-AS1 was down-regulated in bovine mammary epithelial cells and mammary tissues under inflammatory condition. Knockout (KO) of LRRC75A-AS1 by CRISPR-Cas9 system in bovine mammary alveolar cell-T (MAC-T) cell line could enhance expressions of tight junction (TJ) proteins Claudin-1, Occludin and ZO-1, reduce cell monolayer permeability, and inhibit Staphylococcus aureus adhesion and invasion. Meanwhile, it also down-regulated expressions of inflammatory factors and attenuated activation of NF-κB pathway. Similarly, knockdown of LRRC75A caused the changes as LRRC75A-AS1 KO did, while overexpression of LRRC75A enabled the opposite effects. TJ of epithelioid cells barriers the pathogenic microorganisms outside during inflammation, in which LRRC75A-AS1 can regulate the expression of TJ proteins through LRRC75A, affecting the development of inflammation.